Teaching and assessing intercultural communicative competence - Byram, Michael (Clevedon ; Philadelphia : Multilingual Matters, 1997)
Byram aims to define precisely what competencies are required in foreign and second language learning, how these can be included in teachers' objectives and methods, and how the ability to communicate across cultural difference can be assessed.
-- 1. Defining and Describing Intercultural Communicative Competence -- 2. A Model for Intercultural Communicative Competence -- 3. Objectives for Teaching, Learning and Assessment -- 4. Curriculum Issues -- 5. Assessment.
Includes bibliographical references (pages 116-120) and index.
Keywords: Language and languages -- Study and teaching; Multicultural education; Intercultural communication -- Study and teaching; Communicative competence